醫學的工具理性與儒家的中庸之道: Instrumentalist Relationality in Medicine and the Confucian Middle Way - ZHENG, Linjuan (International Journal of Chinese & Comparative Philosophy of Medicine, 2009)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 中國現代社會醫學領域中出現的種種怪異現象，不幸印證了這樣一個事實：現代醫學的發展與人類發展醫學之真實目的顯現出背道而馳的趨向。本文以上海某醫院一系列引人深思的事件解析其中的原因，規範醫院的行為確實離不開外在的監督，但筆者認為更深層次的原因是科學主義所導致的現代科學迷信和個別醫務工作者的私慾膨脹，最終歸結為工具理性膨脹對上海某醫院一系列引人深思的事件難辭其咎。針對以上弊端，我們可以從中國儒家思想中尋找到應對的思想資源：首先闡明儒家對科學技術的態度；其次闡明儒家的義利觀；最後闡明儒家的科技態度和義利觀得以實現的路徑——中庸之道。通過對儒家思想的現代轉化，可以用於超越和克服現代醫學領域中的工具理性弊病。 Recent years have witnessed various unusual events in the medical field in China. This essay explores one particular event that has attracted intense attention and generated broad discussion: the use of a new but unapproved and unaccredited medical technique in a large Shanghai hospital that caused the death of a patient. Also examined are the series of incidents that led up to this tragic occurrence. Such events and incidents indicate that modern scientific medicine in China has taken a direction that may not be consistent with medicine as health care. Specifically, recent medical developments show an instrumentalist rationality – medicine as a tool for scientific development rather than the treatment of illness and disease. This essay argues that the trend in China towards scientism and instrumentalism in medicine must be overcome by drawing on the moral and intellectual resources of Confucianism. It contends that the Confucian middle way is exactly what is needed to change the current direction in Chinese medical development. First, Confucianism sees science and technology as tools for human flourishing. The current focus on scientism – which seems to hold that science and technology have intrinsic values – is mistaken and should be corrected. Chinese medical technological innovation and application must be directed and mediated by the Confucian moral values of human flourishing and happiness. Second, Confucianism does not reject the gaining of material wealth or medical profit through the practice of medicine, but does require that medical activities be constrained by Confucian virtues, including humanity and righteousness, to ensure that unrighteous profit is not made. The essay concludes by contending that the practice of medicine should be based on embracing the so-called middle way, namely, Confucian virtues and moral concerns, rather than pursuing advanced scientific and technological development. DOWNLOAD HISTORY | This article has been downloaded 134 times in Digital Commons before migrating into this platform.